2017
DOI: 10.1155/2017/8276136
|View full text |Cite
|
Sign up to set email alerts
|

Brain Symmetry Index in Healthy and Stroke Patients for Assessment and Prognosis

Abstract: Objective. Quantitative neurophysiological signal parameters are of value in predicting motor recovery after stroke. The novel role of EEG-derived brain symmetry index for motor function prognostication in the subacute phase after stroke is explored. Methods. Ten male stroke patients and ten matched healthy controls were recruited. Motor function was first assessed clinically using the MRC score, its derivative Motricity Index, and the Fugl–Meyer assessment score. EEG was subsequently recorded first with subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 19 publications
3
56
1
Order By: Relevance
“…Electroencephalography (EEG), or recording the brain’s electrical activity, has been explored as a diagnostic and prognostic tool in stroke 6 , 7 . When cerebral blood flow (CBF) drops during ischemia, abnormalities such as decreases in fast frequencies are observed 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalography (EEG), or recording the brain’s electrical activity, has been explored as a diagnostic and prognostic tool in stroke 6 , 7 . When cerebral blood flow (CBF) drops during ischemia, abnormalities such as decreases in fast frequencies are observed 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, also the inter-hemispheric balance could be studied with qEEG metrics as the brain symmetry index (BSI), that provides a measure of inter-hemispheric EEG power asymmetry not specific to single frequency bands (van Putten and Tavy, 2004 ; van Putten, 2007 ). The BSI is mainly used in the research field for the purposes of stroke prognosis: literature shows that in acute stroke patients a high BSI is positively correlated with a worse neurological status (van Putten and Tavy, 2004 ; van Putten, 2007 ) and with a weaker motor recovery 2 months after the acute event (Agius Anastasi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of M. E. Wolf et al (2017), it was found that generalized (bilateral) changes of the bioelectric activity of the brain reflect the severity of supratentorial structures damage in patients with cerebral ischemic hemispheric stroke, not the focal ones [19]. The numerous studies demonstrate a high diagnostic informative value of the integral EEG pattern coefficients, which reflect the severity of slowwave activity within the assessment of the severity of acute brain damage of ischemic and traumatic genesis [2,4,5,17]. The conducted study allowed us to obtain data on reciprocal changes in the anterior and posterior gradient of EEG pattern rhythms in patients with SSICH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the overwhelming majority of scientific research related to the study of the functional state of cerebral structures within brain injuries of various origins with the use of spectral analysis of bioelectric activity of the brain was aimed at the determination of isolated parameters that are associated with clinical and neuroimaging data and the outcome of the disease [4,7,10,17]. Besides, it is necessary to mention that this monoparametric approach has restrictions, since the functional state of the brain in patients with brain damage in supratentorial localization is a very complex and extremely variable set of relied changes of absolute power, structure, zonal distribution of rhythms of different ranges in affected and intact hemispheres, as well as interhemispheric rhythm asymmetry [2].…”
Section: а а кузнецовmentioning
confidence: 99%